NAXALISM: A SOCIOLOGICAL PERSPECTIVE - Kumar Yadav, Dr. Vinod (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2019)
India is a subcontinent of nationalities, where people of different castes, creed and religion coexist in unity. This ‘unity in diversity’ is the key to the smooth functioning of society. As per the Directive Principles of State Policy, it is the aim of the state to create such type of social and economic conditions under which the citizens can lead a good life. Any manner of oppression on any section of society will cause unrest and eventually the upheaval of uproar in the whole society.